ANALISIS RASIO PENDAPATAN APBN DAN AKREDITASI PADA BADAN LAYANAN UMUM PENDIDIKAN - Martha Carolina (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2021)
APBN revenue is one of the sources of revenue to public service agencies (PSA/BLU) as a source of providing services to the public in accordance with their duties and functions. The quality of public services and the quality of the BLU institutions is reflected by the quality of the accreditation of the BLU institutions. This study aims to determine the effect of APBN revenues on the accreditation ofBLU of education. Purposive sampling was chosen as the method of sampling and 180 samples are obtained from 60 universities for 3 years. The research results of the study show there is a relationship between the ratio of APBN revenue allocation to accreditation at BLU of education and the allocation of income ratios at accredited BLU is different from non-accredited BLU education.